MENGUKUR KEPUASAAN MAHASISWA STIA LAN BANDUNG TERHADAP PELAYANAN ADMINISTRASI KANTOR PELAYANAN PAJAK DI ERA REFORMASI PERPAJAKAN - Rahman, Abdul (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2011)
It is undenaibly uneasy to maintain and improve services, especially when the target of services is to increase every year. Tax Offices are the main pillar in tax collection from the tax payers ? among them are STIA LAN Bandung students. To identify the students' satisfaction toward the administrative services of the tax offices, the writer conducted a survey. The result shows 45.5% respondents feel 'satisfied' with the services. 9.1% respondents even consider regard the as 'vey satisfied'. Only 3.6% judge them as 'dissatisfied' and 1.8% 'very dissatisfied'.